Representasi Single Parent dalam Film Susah Sinyal - Muhammad Faisal Wisnu Ananta Putra (CHANNEL: Jurnal Komunikasi, 2019)
The Susah Sinyal movie is a lm that takes the theme of the life of a singleparent woman in carrying out her role. single parent is a picture of a single parent who is very tough because they have to play both roles as father andmother. The purpose of conducting research is to show how the stereotypical representation of single parent women in lm Susah Sinyal. This type of research used in this udy is a qualitative udy using the Roland Barthessemiotic analysis method. This research focuses on the role of a single parentwoman named Ellen who is represented in the lm. The results of this udy indicate that the stereotypical representation of single parent is shown in 3 (three) categories. First, the stereotype representation of single parent womenthat describes emotional women and women who are weak in carrying outboth roles. Second, the representation of women’s resi ance based on liberal feminism which shows the stereotype that single parent women are hard-working women. Third, the representation of patriarchal ideology found aereotype that problem children are the failure of single parent women ineducating and caring for children.